(Re)Seeing Black girls: intersections of liberalism, difference, and the hidden curriculum. Issue 4 (2nd October 2017) - Porterfield, Laura Krystal
Abstract : This article analyses the race and gender norms embedded in the verbal and visual discourse at an internationally acclaimed secondary magnet school in Philadelphia. While scholars have documented the visual learning of adolescents and elementary school-aged youth of colour extensively, few have focused exclusively on the nature of visual learning for young Black women in and around urban schools. The nature of looking and the visual is a highly contested and political process in the twenty-first century urban context. Images saturate the cityscape; these images teach. Thus this article examines the specific lessons related to race, gender, and place young Black women learn from the school adults who shape the visual culture of their school environment. Based on an ethnographic, photographic and discourse analysis study, this article argues that even in the context of an award-winning, progressive, liberal-minded school culture, young working class Black women are often softly encouraged to change and or are re-programmed into more palatable, commodifiable versions of themselves that both sustain and advance the school's identity as different. This 're-programming' often requires young Black women to alter their dress, speech, and physical demeanour in order to find belonging in a larger school culture dominated by a discourse of inclusivity and diversity.